Gamification as a motivational and dynamic strategy for higher education - Gaspar Huamaní, Edith (2021)
This investigation focuses on gamification as a teaching -learning strategy that arouse the interest of universities students to learn significantly and allows the teacher to evaluate his methodology and plan the most dynamic and motivating classes to promove environments where students can be motivated so they can participate , increase their learning and be competitive. Also, it describes positive aspects of gamification for teacher and student. In order to be a teacher’s good subject, he needs to gamify the class and content considering the elements of the gamification .In addition, It proposes three successful free access tools to gamify classes: kahoot!,Quizizz and Socrative.